(untitled) (Research, Society and Development, 2020)
Objective: to analyze the unplanned withdrawals of invasive devices in an intensive care unit. Method: this is a cross-sectional, descriptive, documentary study carried out at a university hospital in Rio de Janeiro. Data collection took place on the control forms of invasive devices, from February to September 2018. The data were analyzed using simple and inferential descriptive statistics. Results: 2292 records were consulted, which resulted in the analysis of 7,098 invasive devices / day. Of these, 115 had unplanned withdrawals, corresponding to a rate of 16.2. Most unplanned withdrawals occurred with enteral tubes (76), with the main reason for withdrawal by the patient himself (55- 72.4%). Conclusion: the analysis of withdrawals, allows the adoption of strategies and actions that act to prevent the withdrawal of these devices.